Spanish Education Inspectorate (CIE): Access and Training - Tébar Cuesta, Fernando (Avances en Supervisión Educativa, 2025)
The aim of this essay is to reflect on the selection and training of education inspectors in Spain. The selection of officials for the Education Inspectorate is first discussed, reflecting and analysing from various perspectives including the necessary training, the meritocratic system, the tribunals and examinations, and offering innovative proposals to ensure that selection processes attract and retain the best talent as far as possible. Secondly, the objective is strategic planning, for a fully flexible and adaptive training to develop their specific skills and abilities so that they can face current and future challenges, characterized by a linear movement in many aspects (classical opposition) but exponential in others (IA). Finally, in order for these new Inspectors of education to comply with the principles of effectiveness and efficiency in the 21st century, a modular training is proposed in the form of a dynamic combination of traditional values and skills required by the present environment.